Thailand’s Destination Image and Intention to Visit Perception Tourist in Indonesia - Sunchai Gamon; Asnee Malee (Research Collaboration Community (RCC), 2022)
Thailand isa popular tourist country in southeast Asia where millions of tourists come to visit each year. However, most of the first visitors left the question why so few people have tourist behavior back to the destination of Thailand. The study is to find out how the image of destinations, access surveys affect the behavior behavior through the satisfaction of Indonesian tourists on the travel destination in Thailand. The research method used is quantitative, sample retrieval technique using non-sampling and obtained samples as much as 385 respondents, the analysis tools used are path analysis and hypotheses using the import analysis tools used by Amos and SPSS. The study suggests that the live test of destination image and access reading variables affected the behavioral test of Indonesian tourists on Thai tour destinations and then for the satisfaction of tourists able to improve the relationship between the image of destinations and the behavior of Indonesian tourists on the Thai tour destinations, it contributed by reviewing the behavior patterns of tourists in Indonesia while visiting the destination of tourism. The academic and managerial implications of this discovery are useful in devising a tourist destination country tourism strategy in Thailand.